BEVA primary care clinical guidelines: Analgesia. (10th December 2019) - Bowen, I. M.; Redpath, A.; Dugdale, A; Burford, J. H.; Lloyd, D.; Watson, T.; Hallowell, G. D.
Summary: Primary care guidelines provide a reference point to guide clinicians based on a systematic review of the literature, contextualised by expert clinical opinion. These guidelines develop a modification of the GRADE framework for assessment of research evidence (vetGRADE) and applied this to a range of clinical scenarios regarding use of analgesic agents. Key guidelines produced by the panel included recommendations that horses undergoing routine castration should receive intratesticular local anaesthesia irrespective of methods adopted and that horses should receive NSAIDs prior to surgery (overall certainty levels high). Butorphanol and buprenorphine should not be considered appropriate as sole analgesic for such procedures (high certainty). The panel recommend the continuation of analgesia for 3 days following castration (moderate certainty) and conclude that phenylbutazone provided superior analgesia to meloxicam and firocoxib for hoof pain/laminitis (moderate certainty), but that enhanced efficacy has not been demonstrated for joint pain. In horses with colic, flunixin and firocoxib are considered to provide more effective analgesia than meloxicam or phenylbutazone (moderate certainty). Given the risk of adverse events of all classes of analgesic, these agents should be used only under the control of a veterinary surgeon who has fully evaluated a horse and developed a therapeutic, analgesic plan that includes ongoing monitoring for such adverse events such as the development of right dorsal colitis with all classes of NSAID and spontaneous locomotor activity and potentially ileus with opiates. Finally, the panel call for the development of a single properly validated composite pain score for horses to allow accurate comparisons between medications in a robust manner.